Anxiety, self-esteem and competition ranking of judokas - Kolayis, H.; Sari, I. (Archives of Budo, 2011)
Background and Study Aim: The aim of this study was anxiety, self-esteem, self-confidence levels and competition ranking of Turkish judokas, the relationship of these variables with competition ranking.